Penerapan Metode Profile Matching untuk Pendukung Keputusan Pemilihan Manajer Information Technology - Anita Diana; Dwi Achadiani; Hendri Irawan (Jurnal Teknik Informatika dan Sistem Informasi, 2021)
The selection of an IT manager in a company has an important role in a decision, because a manager occupies a managerial level position who will make decisions later. The current process of selecting IT managers is still being carried out conventionally, resulting in several problems. Among them, the assessment is carried out manually so that the calculation process can occur errors and take longer, then which alternative is the best according to the recommendation of the decision support system (DSS) application. To overcome some of these problems, a DSS was designed which resulted in more precise and effective decisions. The method used is the Profile Matching method which is used to determine alternative rankings, where the criteria and weight values ??have been determined and are contained in the assessment document. This research produces a web-based DSS application that helps decision making in selecting IT managers. This DSS application will simplify the calculation of the assessment thereby reducing calculation errors. The end result of implementing DSS for the selection of IT managers is that the selection process becomes more precise, effective and objective